ANALISIS BUDAYA KERJA MAPALUS DALAM PENGEMBANGAN SPIRITUALITAS KERJA DOSEN DAN STAF DI JURUSAN PARIWISATA - Pearl Loesye Wenas; Seska Meily Mengko; Meiske Martha Sangian (HOSPITALITI DAN PARIWISATA, 2022)
MAPALUS WORK CULTURE ANALYSIS IN DEVELOPING THE SPIRITUALITY OF LECTURERS AND STAFF IN THE TOURISM DEPARTMENT1)Pearl Loesye Wenas, 2 Seska M.H. Mengko1,2)Politeknik Negeri Manado. 1)lusyepearl74@gmail.com Jl Kampus Politeknik Desa Buha Kecamatan Mapanget2)seskamengko@gmail.comAbstractThe purpose of this research is to analyze the effect of Mapalus work culture in developing the work spirit of lecturers and staff employees in the tourism department. This study uses a descriptive qualitative research method that describes the actual phenomenon of MAPALUS work culture in developing the work spirituality of lecturers and staff in the tourism department. The research showed that Mapalus work culture is still relevant in the tourism department, seen from the practice of Mapalus values in the tourism department's work environment. Lecturers and staff synergize in helping and building the department more on participatory values, discipline, leadership, solidarity and responsibility which are the main indicators in the application of MAPALUS culture. This is part of an effort to develop work spirituality to achieve the goals of lecturers and staff in their work. The development of work spirituality is seen from how lecturers and staff develop strong relationships with coworkers and other people related to work including creativity, communication, respect, partnership, positive energy, flexibility and fun. Having consistency or harmony between one's beliefs on organizational values, sharing and experiencing love, interest in being together with one another in work units and the organization as a whole are also part of developing work spirituality in the tourism department.Keywords: work culture, mapalus, work spirituality